Differential predictive value of PTSD symptom clusters for mental health care among Iraq and Afghanistan veterans following PTSD diagnosis. (October 2017) - Smith, Noelle B.; Tsai, Jack; Pietrzak, Robert H.; Cook, Joan M.; Hoff, Rani; Harpaz-Rotem, Ilan
Abstract: Objectives: Veterans from the recent conflicts in Iraq and Afghanistan are being diagnosed with posttraumatic stress disorder (PTSD) at high rates. This study examined characteristics associated with mental health service utilization, specifically psychotherapy, through the Department of Veterans Affairs (VA), in a large cohort of Iraq and Afghanistan veterans newly diagnosed with PTSD. Method: This study utilized national VA administrative data from Iraq and Afghanistan veterans following an initial diagnosis of PTSD and completed a self-report measure of PTSD symptoms between Fiscal Years 2008–2012 (N=52, 456; 91.7% male; 59.7% Caucasian; mean age 30.6, SD=8.3). Regression analyses examined the relation between PTSD symptom cluster severity and treatment-related variables. Results: Accounting for demographic/clinical variables, PTSD symptom clusters were related to psychotherapy initiation (re-experiencing, OR=1.23; numbing, OR=1.15), combination treatment (medication and psychotherapy; re-experiencing, OR=1.13; avoidance, OR=1.07; dysphoric arousal, OR=1.06), number of psychotherapy visits (re-experiencing, IRR= 1.08; numbing, IRR=1.09), and adequate dose of therapy (e.g., 8 visits/14 weeks; re-experiencing: OR= 1.07). Conclusions: When considering treatment approaches for trauma-exposed veterans, it is important to map the severity of unique PTSD symptoms clusters; this may have implications on the selection of treatment that best fits the veterans' needs and preferences (e.g., exposure therapy versus cognitive processing therapy). Highlights: PTSD symptom clusters uniquely relate to initiation and remaining in psychotherapy. PTSD symptoms clusters should be considered when veterans are newly diagnosed. The severity of unique PTSD symptoms clusters affects treatment-related variables. Re-experiencing and numbing are critical in therapy initiation and retention. Treatment selection should be tailored to best fit veterans' symptom presentation.